2018
DOI: 10.5539/jel.v7n3p11
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions as Drivers for Improving Inclusion in Teaching Pupils with Special Educational Needs

Abstract: The aim of this paper is to enhance understanding of the contradictions that arise in the drive to improve teaching practices among pupils with special educational needs (SENs). A questionnaire was administrated to 167 classroom teachers, subject teachers, special education teachers and teaching assistants in Finland. The analysis, based on thematic coding and analysis of manifestations of contradictions, revealed contradictions related to artefacts of teaching, participation in the community and school staff’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…Furthermore, they expressed mostly positive attitudes towards the support system and their own role in its implementation. This interesting result is somewhat different from those reported in previous studies (Paju et al 2016(Paju et al , 2018OAJ 2017). In accordance with the study conducted by the Trade Union for Education (OAJ 2017), teachers had a negative view of the support system and their own capability in supporting pupils with learning disabilities in the general class.…”
Section: Collegial Collaboration and Consultationcontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, they expressed mostly positive attitudes towards the support system and their own role in its implementation. This interesting result is somewhat different from those reported in previous studies (Paju et al 2016(Paju et al , 2018OAJ 2017). In accordance with the study conducted by the Trade Union for Education (OAJ 2017), teachers had a negative view of the support system and their own capability in supporting pupils with learning disabilities in the general class.…”
Section: Collegial Collaboration and Consultationcontrasting
confidence: 99%
“…Approximately one-third of the responding teachers experienced a lack of knowledge concerning teaching pupils at the third tier of support (Paju et al 2016). In another study, Paju et al (2018) showed that teachers lacked sufficient special educational knowledge and time to be able to provide good general education for all pupils whilst also offering adequate support to students with learning difficulties.…”
Section: Inclusive Education and Teachers' Competencementioning
confidence: 99%
See 3 more Smart Citations